(3GdGcJaG aj eZGRj GdeUWai hGdKdGKI GdNdaGs - (3GdcdGYj , SdjeGf Hf ehSi Hf SGde Hf MSGf GdMejQj, CHh GdQHjY,J (B634 (3g` s
(3ChdgG (B:s
(3hPcQ GHf YHOGdMcje Yef SeGg ef TjhNfG s
(3BNQgG (B:s
(3jRhQc Yf TMW GdeRGQ oeSdekG ajdbGc HGdENdGU de jJfcH s
(3ef fSNI KGefIs
(3hgh BNQ GdcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B136 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B399s
Keywords: (3GdJGQjNs